Serving Society Through Community Enterprises : A Case Study on ARSU Knit Project, Nepal - Nayak, Venkatesha; Hegde, Kavya P. (AMC Indian Journal of Entrepreneurship, 2019)
The paradigm change in entrepreneurship has made real sense by taking societal problems seriously. Today, social entrepreneurship is playing a key role as the sense of eco friendliness and environmental consciousness is growing in the market. The economic imbalance in the society doesn’t make much difference to some extent as poverty has been justified as a necessity. In the time of modernization, the diversion towards societal issues have been targeted greatly, and because of these efforts, social enterprises are budding up. However, with the wide ideas behind the knowledge, still the struggle continues to define social entrepreneurship. To make it simpler, a similar objective is termed here as community enterprise, which aims at societal good. In this context an attempt has been made in this paper to discuss the role of community enterprises in sustainable development. In this paper, a case study on ARSU Knit Project of Nepal was presented which made the difference in the lives of people through entrepreneurial activity. In the year 2015, Nepal was hit by earthquake ad most of the affected area people lost hopes. Arya K. C., who is from Nepal but graduated from India, came up with idea of bringing sunshine back in their eyes, with the help of Community Network Without Border (CWB), an organization in which participants are independent but mutually cooperate and support each other without having barriers of border. Arya started contacting people, sheltered them under an umbrella,and served them by engaging them in knit work. As a charitable organization, CWB started collecting woollen rolls from households of Japan and supplied the same to people of affected area as a support, and today their products are reaching the market. It has made them self sufficient through entrepreneurial activity. The data were collected primarily through interview and mail conversations with the objective to understand community activity undertaken by ARSU Knit project of Nepal and the same has been discussed in detail in the paper.